Poverty and inequalities: an obligatory dental health debate - Abadía Barrero, César Ernesto (Acta Bioethica, 2006)
Latinamerican last decades' health reforms have encouraged liberal principles where access to services depend on purchasing power, and where emphasis is placed more on therapeutics than on prevention. Therefore, people with high income present less sickness risks while those with low income are more vulnerable to illness due to their poor access to health services. This situation is even worse in oral health issues; that's why bioethics is urgently required to act as speaker in a debate on equity.